Hematological Parameters Characteristics in Children with Obstructive Sleep Apnea with Obesity - Shen T; Wang J; Yang W; Li L; Qiao Y; Yan X; Chen M; Tang X; Zou J; Zhao Y (Dove Medical Press, 2021)
Tian Shen,1,* Jing Wang,1,* Wen Yang,1 Linke Li,1 Yixin Qiao,1 Xiaohong Yan,1 Min Chen,2 Xiangdong Tang,3 Jian Zou,1 Yu Zhao1 1Department of Otorhinolaryngology Head and Neck Surgery, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2Department of Otorhinolaryngology Head and Neck Surgery, Chengdu Shangjin Nanfu Hospital, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 3Sleep Medicine Center, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yu Zhao; Jian ZouDepartment of Otolaryngology Head and Neck Surgery, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of ChinaTel +86-18980601410; +86-18980605883Email yutzhao@163.com; zoujian926@163.comObjective: To investigate the possible correlation between obesity and hematological parameters in children with obstructive sleep apnea (OSA).Methods: A total of 460 children was initially included in our study, which were divided into children with OSA and children without OSA. Multiple analysis was performed for obesity by adjusting confounding factors such as age and gender in 460 children. Further, to minimize the influence of confounding factors and selective bias, propensity score matching (PSM) was performed in children with OSA. Hematological parameters such as inflammatory and coagulable parameters were compared between the normal weight children with OSA and the obese children with OSA following PSM.Results: OSA (OR = 3.061; P< 0.001; 95% CI, 1.772– 5.288) represented an independent risk factor for obesity. Besides, the obese children with OSA had higher levels of white blood cell (WBC) (P< 0.001), neutrophil (NEUT) (P< 0.001), neutrophil-lymphocyte ratio (NLR) (P=0.006), fibrinogen (FIB) (P=0.033), while had a lower level of activated partial thromboplastin time (APTT) (P=0.048). No significant differences were observed in other hematological parameters. In linear regression, the results indicated that the levels of WBC (R2 = 0.123, Beta = 0.289, P< 0.001), NEUT (R2 = 0.124, Beta = 0.282, P< 0.001), NLR (R2 = 0.105, Beta = 0.184, P=0.026) and FIB (R2 = 0.086, Beta = 0.246, P=0.003) were positively correlated with BMI, while the level of APTT (R2 = 0.057, Beta = − 0.171, P=0.044) was significantly negatively correlated with BMI.Conclusion: OSA was an independent risk factor contributing to obesity. WBC, NEUT, NLR, FIB and APTT are correlated with obesity in children with OSA (aged from 2 to 14 years). These indicators could be used to estimate the status of inflammation and hypercoagulation in the obese children with OSA.Keywords: obstructive sleep apnea, obesity, propensity score matching, hematological parameter, inflammation, hypercoagulation